2015
DOI: 10.1016/j.cbpa.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

LOV-based reporters for fluorescence imaging

Abstract: Chromophore-binding domains from plant and bacterial photoreceptor proteins have recently gathered increasing attention as new sources of genetically encoded fluorescent proteins (FPs). In particular, FPs based on the flavin-binding LOV (light, oxygen, or voltage sensing) domain offer advantages over green fluorescent protein (GFP) owing to their smaller size, pH and thermal stability, utility under anaerobic conditions and their ability to generate reactive oxygen species. This review focuses on the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
102
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(109 citation statements)
references
References 57 publications
2
102
0
Order By: Relevance
“…For instance, a recent publication has demonstrated that the subset of F-actin that is recognized by diverse ABDs can be altered by the fluorescent protein or the linker sequence between the ABD and the fluorescent protein (Lemieux et al, 2014). New applications for fluorescent labeling of proteins have become available recently, such as the use of Y-FAST, a small monomeric protein tag enabling reversible binding and activation of a cell-permeant and nontoxic fluorogenic molecule (Plamont et al, 2016), or the flavoprotein improved LOV (iLOV), a fluorescent protein based on the light, oxygen or voltage domain (LOV) from a variety of sources (Buckley et al, 2015). Both molecules offer advantages over GFP and other related fluorescent reporters owing to their relatively small size.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a recent publication has demonstrated that the subset of F-actin that is recognized by diverse ABDs can be altered by the fluorescent protein or the linker sequence between the ABD and the fluorescent protein (Lemieux et al, 2014). New applications for fluorescent labeling of proteins have become available recently, such as the use of Y-FAST, a small monomeric protein tag enabling reversible binding and activation of a cell-permeant and nontoxic fluorogenic molecule (Plamont et al, 2016), or the flavoprotein improved LOV (iLOV), a fluorescent protein based on the light, oxygen or voltage domain (LOV) from a variety of sources (Buckley et al, 2015). Both molecules offer advantages over GFP and other related fluorescent reporters owing to their relatively small size.…”
Section: Discussionmentioning
confidence: 99%
“…The key advantages of using phiLOV2.1 as a reporter are its stability over a wide range of pH values, its molecular oxygen independency and its small size (12.1 kDa). Conversely, photobleaching, and weaker signals are disadvantages (Buckley et al, 2015). Recently, protein translocation into mammalian cells through the type 3 secretion system of Shigella flexneri was successfully visualized using phiLOV2.1 (Gawthorne et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, protein translocation into mammalian cells through the type 3 secretion system of Shigella flexneri was visualized using phiLOV2.1, an improved version of LOV (Gawthorne et al, 2016). The LOV domain is responsible for the fluorescence properties of the plant blue-light receptor kinases called phototropins, regulated either by Light, Oxygen or Voltage (Huala et al, 1997;Buckley et al, 2015). Compared with LOV phiLOV2.1 has increased fluorescence and photostability (Christie et al, 2012a,b).…”
Section: Introductionmentioning
confidence: 99%
“…All systems that rely on endogenous chromophores are based on one of three compounds: flavin mononucleotide (FMN), biliverdin, or bilirubin (Figures and , Table ). Systems that rely on complexation of FMN are typically non‐covalent complexes that fluoresce in the cyan‐green wavelength range . These systems are based on bacterial photoreceptors comprised of light, oxygen, and voltage (LOV) sensing domains, which form a reversible covalent bond with FMN via a conserved cysteine residue over the course of their photocycle.…”
Section: Introductionmentioning
confidence: 99%